Gosudarstvennoe upravlenie v sfere sporta za rubežom: opyt Velikobritanii - Dolmatova, T. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
This article discusses the institutional framework for sports policy in the United Kingdom of Great Britain. While being the leading sporting power in the world Great Britain provides a successful system of sport governance. Study Aim: is the research of the model of sport governance on the example of British national governing bodies. An institutional approachwas applied to study the organizational structure of sport governance in the United Kingdom. In the course of the work the following research methods were used: analysis of literary sources, generalization, case-study, method of expert evaluation. The activities of the main UK agencies and organizations in the sphere of sports including national governing bodies are circumstantially considered, the main legal documents defining sport policy are analyzed as well. The strong sport governance system contributes to the high sporting results of the British national governing bodies in the basic kinds of sport. Therefore it is recognized that the United Kingdom as a leading world sporting power conducts a systematic policy in the sport governance, being a leader in this sphere.